Communication of anger versus disappointment in bargaining and the moderating role of power. (22nd February 2018) - van Dijk, Eric; van Beest, Ilja; van Kleef, Gerben A.; Lelieveld, Gert‐Jan
Abstract: Emotional expressions can have a pervasive impact on bargaining behavior and outcomes. This widely documented phenomenon implies that in their communications, bargainers may adjust their apparent emotions. In the current paper, we developed a paradigm to study the communication of anger and disappointment, two of the most commonly experienced emotions in bargaining. The results of three experiments show that bargainers often adjust the intensity of their emotions in their communicated emotions. The findings show a differentiated pattern, revealing that bargainers rather exaggerate their disappointment than their anger, especially when the target of their communication is in a high power position. The results are discussed and related to the social functional approach of emotions.